2021
DOI: 10.1111/cob.12447
|View full text |Cite
|
Sign up to set email alerts
|

Diet, eating behaviour and weight gain in men and women with overweight/obesity receiving varenicline for smoking cessation

Abstract: Because trying to quit smoking and not gain weight requires changes in two major behaviours simultaneously we explored eating behaviour in smokers with overweight/obesity making a quit attempt using guideline-based treatment. Participants were randomized to a carbohydrate-reduced or fat-reduced diet. The Three Factor Eating Questionnaire and Binge Eating Scale were completed by 48 of 64 participants in the low-carbohydrate and 47 of 58 in the fat-reduced group at randomization, after 6 and 14 weeks. At 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…5 In certain research, cognitive constraint has been associated to greater weight gain in people of normal weight, however in other studies, it has been connected to decreased food cravings and a decreased risk of obesity. [6][7][8] Hunger and emotional eating have both been linked to higher BMIs and obesity. 9 It has also been suggested that emotional eating acts as a bridge between sadness and weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…5 In certain research, cognitive constraint has been associated to greater weight gain in people of normal weight, however in other studies, it has been connected to decreased food cravings and a decreased risk of obesity. [6][7][8] Hunger and emotional eating have both been linked to higher BMIs and obesity. 9 It has also been suggested that emotional eating acts as a bridge between sadness and weight gain.…”
Section: Introductionmentioning
confidence: 99%